Analysis of Speaking Skills with Storytelling Method in Indonesian Language Learning in Elementary Schools - Nidya Chandra Muji Utami; Siti Fatimah Azzahra; Nuryani Nuryani (research, training and philanthropy institution Natural Aceh, 2023)
This literature study, entitled